Il restauro dell’impianto idraulico della grotta degli Animali, a Castello - Tesi, Valerio (Opus Incertum, 2019)
The Grotto of the Animals in the garden of Castello was famous for its water features: tens of jets hidden among the stones in the vault and in the floor. To obtain this effect, the structure conceals a complex hydraulic system now investigated with a laser scanner survey that highlighted the path of the ancient pipelines above and around the grotto. The research has contributed to the project of conservation of the monument and to the reactivation of the hydraulic system. When the floor of the terrace above the grotto was covered with paving stones during the Lorraine era the earthenware conduction network, the sandstone fittings and the lead piping, which probably no longer worked at the time, were concealed once and for all. As a consequence, a fundamental component of the sixteenth-century hydraulic system was lost. After a first, initial phase in which the various internal decorations were secured and restored, a series of investigations and progressive inspections were initiated in order to carefully bring to light the whole hydraulic system and its layout above the vaults of the grotto. The aim was then to understand how it originally worked and to assess whether the water features could be reactivated as possible solutions for the grotto's roof in relation to the current layout of the Appennino level. As Giorgio Vasari wrote, the water falling inside the grotto ‘sounds sweet to the ear and is beautiful to the eye’. Therefore, so as to restore a fundamental element of the Grotto of the Animals, the next task was to figure out how to reactivate the hydraulic system in the extrados. First of all, after a series of cautious tests, the narrow lead pipes threading through the vaults, blocked by encrustations, deposits and materials that had hardened in time, were reopened by making perforations from the inside. Instead of replicating the sixteenth-century loop system, a different method was adopted to conduct the water to the rainfall nozzles. Every nozzle inside the grotto was given new autonomous and independent tubing connected to new collectors in the side ducts of the grotto to conduct the water. As a result, precise checks can be made of the water pressure and the system is easy to maintain.